Pengaruh Penggunaan Celebrity Endorser terhadap Minat Beli Produk Bittersweet by Najla Lampung - Aska, Diajeng Sekaratu Galuh; Melsandi, Depi (https://jurnal.binamandiri.ac.id/, 2022)
This paper aims to determine the effect of using celebrity endorsers on buying interest in Bittersweet by Najla Lampung products. The object of this research is consumer interest in buying Bittersweet by Najla Lampung products. This research uses quantitative research. The data processing technique uses the help of the SmartPLS3 application. The data collected by the researchers used a questionnaire to the respondents with a sample of 57 respondents. The results showed that partially the use of celebrity endorsers had a positive and insignificant effect on buying interest in Bittersweet by Najla products.